Clinical Technologies for Providing the Quality of Dental Orthopedic Treatment Using Patient-Oriented Innovations on Base of Material Science - Yanishen, I.; Fedotova, Olena; Youchenko, P.; Yarova, A.; Andrienko, K. (My University, 2019)
The development and implementation of qualimetrical approach to the assessment of existing and new dental materials with the subsequent formation of the high-level complaint in their complexes.
Keywords: dental materials; «material-construction»; compliance; dental construction